"Comparative Silence" Still?: Journalism, academia, and the Five Eyes of Edward Snowden. Issue 3 (16th March 2017) - Ruby, Felicity; Goggin, Gerard; Keane, John
Abstract : This paper revisits the longstanding debate about journalism, academic scholarship, and their connections with the powerful forces of surveillance that shape the lives of contemporary democracies. Drawing critically on the practical findings of Edward Snowden and others, we offer an analysis of the "Five Eyes" intelligence collection and sharing arrangements between the United States, United Kingdom, Australia, New Zealand, and Canada, and the responses it has elicited from journalists and academic researchers. We show how and why journalists and academics have been deterred from researching and reporting on the significance of Five Eyes activities to the public. The paper provides a new account of the Five Eyes project, helped along by the findings of journalists, including the NSA data-gathering schemes exposed by Edward Snowden. Then we examine the uneven outputs of journalists and academics. Finally, we will show why Edward Snowden's revelations must be seen as just one contribution to our understanding of a much longer historical trend; and we show why the work of other, less well-known journalists is vital for explaining and understanding a surveillance programme that arguably has profound threatening implications for the future of journalism, university scholarship, and the ideals and institutions of democratic citizenship.